In the Shadow of No Towers: The anxiety of expression and images of past trauma in Art Spiegelman's graphic novel. Issue 1 (1st April 2014) - Findlay, Laura
This article will examine the anxiety of expression and images of past trauma in Art Spiegelman's graphic novel In the Shadow of No Towers (2004) and its connection to Maus I and Maus II (1986 and 1991). It will analyse the strategies that Spiegelman adopts to deal with trauma, and the problems of representing complex events and narratives. Maus and In the Shadow of No Towers have at their core an anxiety of about the nature of expression; the need to represent the event and the resulting trauma while acknowledging the impossibility of ever fully communicating it. This raises some questions about relations between the present and the past in these texts and the use of highly emotive imagery to make personal and political points about the aftermath of 9/11.